Socio-Economic Modeling of Pamba River Basin in Kerala State using Geospatial Technology - T.V. Padma Priya and S. Jane Mithra (International Journal for Innovative Research in Science & Technology, 2015)
This study provides the socio-economic conditions in correlation with the natural resources and the prevailing demographic characteristics within the natural boundary of Pamba river basin. The study has been carried out using the population statistics of last three decades. This data has been depicted using the Geographical Information system for spatial analysis. The parameters considered for analysis and population model projections are panchayath wise households, total population, population in the age group 0-6, literate population, illiterate population, main workers population, marginal workers population, non-workers population and other thematic layers such as basin boundary, administrative boundaries, land use/ cover map, road-rail network and drainage maps. Various population models were generated to forecast the future population characteristics. The population data of 12 panchayaths which are fully within the Pamba river basin has been taken for analysis and modelling. From this analysis it can be observed that for last decades the socio-economic development of the region is found remarkably good with respect to the living conditions of the people without destroying the land cover pattern of the basin by preserving more than 60% area under forest cover. The study also proves the ability of GIS techniques as a tool in spatial analysis of natural resources management.